THE USE OF WATCHING YOUTUBE VIDEOS FOR ACQUIRING STUDENTS’ LISTENING COMPREHENSION - Fadillah, Arfa S. N.; Nasrullah; Rosalina, Elsa (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2023)
YouTube offers plenty of authentic material created by people worldwide which is frequently used as learning media. Numerous studies on YouTube have been carried out, some of which examined the effect of YouTube on listening ability, and the use of YouTube as learning media. However, only a few studies talk about the use of YouTube on students’ listening comprehension particularly to monitor self-improvement for getting English listening proficiency. Therefore, anchored in Anderson’s (1995) theory and filling the void of previous studies, this research was conducted to describe the use of watching YouTube videos for acquiring students’ listening comprehension. This research applied a qualitative research approach using a structured questionnaire and semi-structured interview as the instruments to collect the data. The subjects of this research were 4 students of the English Language Education Study Program of Lambung Mangkurat University. Findings showed that the use of YouTube videos by the respondents means they use extensive listening to improve their listening comprehension. The participants portrayed using YouTube as a way of self-improvement. The improvement they felt after watching YouTube videos was that they are able to easily find the main idea and general information while listening. It can be concluded that watching YouTube videos frequently is useful enough to improve students' listening comprehension.